Penguatan Karakter Islami Melalui Program Kkn Di Berkah Rumah Belajar Kelurahan Sari Rejo Medan Polonia - Rosdiana, Rosdiana; Naimi, Nadlrah (Journal of Community Sustainability, 2025)
The Community Service Program is a form of community service carried out by university students as an implementation of scientific knowledge and Islamic values in society. This activity aims to strengthen Islamic character education through teaching and role modeling in the social environment. This study aims to describe the implementation strategy of the Community Service Program in strengthening Islamic character education through activities such as teaching Qur’an recitation (ngaji), mosque community service (gotong royong), and competitions for pious children (Anak Sholeh/Sholehah) at Berkah Rumah Belajar, Sari Rejo Subdistrict, Medan Polonia. The research employed a qualitative descriptive method with a participatory approach, in which data were collected through observation, interviews, and documentation over a 13-day period of activity. The results showed that these three activities successfully instilled values of religiosity, discipline, responsibility, and social awareness. Teaching ngaji enhanced children’s spirituality, gotong royong strengthened community solidarity, while the Anak Sholeh/Sholehah competition fostered self-confidence and sportsmanship. Therefore, the KKN program proved effective as a strategy for strengthening Islamic character in society, particularly among young children and teenagers.